The mobility of Researchers and Professionals of Health in Africa: the AFRICA BUILD Project Case Study - Traore, Seydou Tidiane; Anne, Abdrahamane; Bagayoko, Cheick Oumar (Journal of Health Informatics in Africa, 2013)
Background and Purpose: AFRICA BUILD is a coordination action funded by the EU involving 4 African institutions, 3 European and one international. It is designed to promote education and research in the field of health using Information and Communication Technologies (ICT). One of the main objectives of the project is the development of centers of excellence in health and the development of services and mechanisms for mobility. The present work is designed to report the status of the implementation of this mobility. Methods: To achieve mobility, policy and strategy have been defined as a first step. These strategies include defining the scope, duration, criteria and mechanism of mobility. A survey was then conducted to list applications and mobility offerings among the AFRICA BUILD Consortium. Finally, a computer information system has been developed and integrated with the AFRICA BUILD Portal [1] to deliver applications and requests. This work concerns only the mobility of the staff of the institutions of the Consortium. The system can be used by any health professional connected to the AFRICA BUILD Portal. For the financing of mobility of students and researchers from institutional partners of AFRICA BUILD, it is fully ensured by the applicant institution through its budget allocated within the framework of the project. Results: Three mechanisms or types of mobility have been identified: South-South mobility (i.e. between African partners) which is more encouraged, the North-South (i.e. European experts go to African institutions) and the South-North (i.e. African researchers go to European institutions). So far, 203 demands and 31 mobility offers are listed on the AFRICA BUILD Portal. These requests are related initial and continuous training in public health, medical informatics and clinical specialties. The first initiatives are already underway with 5 already completed. Conclusions: In light of the current results, we can say that there are real needs of mobility for researchers and professionals of health in Africa. Considering the important requests made by researchers and professionals outside of the Consortium, it will be very useful to explore the possibility of including a list with possible sponsors willing to fund mobility on the AFRICA BUILD Portal. Keywords: Mobility, E-Health, AFRICA BUILD